The Environmental Issue in the Ecumenical Dialogue - Márquez Beunza, Carmen (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2020)
The ecumenical movement has given increasing attention to the environmental issue, which has become a nuclear dimension of the vision of the oikumene in the 21st century. The ecumenical field has revealed itself as a suitable space for meeting and convergence between Christian Churches. In addition to a scientific question, the environamental crisis is a religious and moral issue. The ecological problem demands a joint response from the Christian faith. This article explores the increasing importance of this issue, from the initial concern for the challenges of a technological world to the proclamation of the work on «Justice, Peace and Integrity of Creation» as a crucial topic in the ecumenical agenda.